H9 subtype influenza vaccine in MDCK single‐cell suspension culture with stable expression of TMPRSS2: Generation and efficacy evaluation. Issue 8 (28th July 2016) - Feng, Lei; Tang, Yinghua; Wu, Peipei; Chu, Xuan; Wang, Weifeng; Hou, Jibo
Abstract : Vaccination is the most effective way to protect chickens from avian influenza pandemics. Mammalian cells, especially MDCK cells, are being investigated as a good alternative to the embryonated chicken eggs for avian influenza vaccine production. In this work, we developed a new MDCK cell line, which has two main features: single‐cell suspension growth and stable expression of human TMPRSS2 protein (transmembrane protease serine S1 member 2) anchored on cells membrane, named MDCK‐Sus‐TMPRSS2. Reverse‐transcription polymerase chain reaction, western blot analysis and indirect immunofluorescence assay were employed to detect the expression of TMPRSS2 in the MDCK‐Sus‐TMPRSS2 cells. Then, H9 subtype avian influenza virus, NJ02/01 strain, was adapted in MDCK‐Sus‐TMPRSS2 cells with serial blind passages and propagated in stirred bioreactor with 9.5 log2/25 μL hemagglutination titers for inactivated avian influenza vaccine production without addition of exogenous trypsin. The MDCK‐Sus‐TMPRSS2 cell‐derived H9 subtype avian influenza vaccine could induce high titers of hemagglutiniton inhibition antibodies in specific pathogen‐free chickens and protect chickens against heterologous H9 subtype influenza virus challenge, showing lower virus shedding rate and sickness rate than in the egg‐derived vaccines group. High titers of H9 subtype‐specific antibodies above 6 log2 were maintained for 6 months in commercial chickens vaccinated by the MDCK‐Sus‐TMPRSS2 cells derived H9 subtype avian influenza vaccine and there were no negative effects on body weight increase in these chickens. Taken together, the results of this work revealed that MDCK‐Sus‐TMPRSS2 cell line could be a promising and safe substitute for embryonated chicken eggs as a host cell line for H9 subtype avian influenza virus propagation.